The Opportunity Criterion: Consumer Sovereignty Without the Assumption of Coherent Preferences - Sugden, Robert (American Economic Review, 2004)
This paper proposes a formulation of consumer sovereignty, for use in normative economics, which does not presuppose individuals' preferences to be coherent. The fundamental intuition, that opportunity and responsibility have moral value, is formalized as an “opportunity criterion” for assessing resource allocation systems. A model of an exchange economy is presented in which rational arbitrageurs compete to make profits by trading with nonrational consumers. In equilibrium, this economy satisfies the opportunity criterion. One interpretation of this result is that, in a competitive environment, the overall effects of money pumps are benign, even if individuals' preferences are unstable or incoherent.